Finding the shortest path in a graph and its visualization using C# and WPF - Radoslav Mavrevski; Metodi Traykov; Ivan Trenchev (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The shortest path problem is a classic problem in mathematics and computer science with applications in Economics (sequential decision making, analysis of social networks, etc.). The presented work is an example of realizing and applying of Dijkstra's algorithm to find the shortest path between two vertices in a connected, undirected graph, which is often a solved problem at a time annual International Olympiad in Informatics. For this purpose, are used the technologies, .NET 4.0, Visual Studio 2010, and WPF for the graphical user interface. The implemented program allows drawing an undirected graph, visualizing the shortest path between two vertices and finding its value. This software is a valuable tool for the study of Dijkstra's algorithm and is a great pedagogic instrument. All figures of path visualization included in this paper are actual screenshots of our visualization program.